Consumable Material Spare Part Management Control in Electricity Transmission System - Widi Riskianto; Iwan Vanany; Niniet Indah Arvitrida (Institut Teknologi Sepuluh Nopember, 2020)
Overstock spare part in the Electric Power Transmission System will affect the inefficiency in the asset management of the company. While the spare part stockouts in the company will disrupt the maintenance process of the electric transmission system, which then lead to power outages. Overstock spare parts are caused by several factors, such as forecasting errors in material requirements, intermittent requests, so it is difficult to determine the optimal order quantity. On the other hand, the unavailability of spare parts will affect the reliability of the electrical energy transmission system, which has the potential in causing a massive power outage. Monte Carlo simulations help to show the more concrete picture of the spare parts inventory condition using a periodic review (R, S) system approach. Divination of the combination of S and R parameters is very influential on the success of spare part control. Spare part classification is used for understanding the demand characteristics and the level of criticism. Moreover, the analysis of simulation results will show the information on supply fulfilment strategies to overcome the problems of either spare parts availability or spare parts overstock.